Management in irrigation of corn hybrids various maturities grown in climatic conditions of Serbia - Dragović, Svetimir; Maksimović, Livija; Radojević, Veljko (Economics of Agriculture, 2010)
Climatic conditions with uneven amounts and variable distribution of rainfall during growing season affect considerably yield performance and stability of crop production. Such conditions are present in Serbia, where droughts of various intensities occur in 80% of the years. Due to such conditions, corn yields are highly variable from year to year which occupies around 40% of the total arable land. The average yield of irrigated corn was 13. 05 t/ha, but of non irrigated corn 11. 14 t/ha. The effect of irrigation was thus 17%. The highest irrigation effect, 33%, was registered in 2007 and 2003 when the largest amount of irrigation water was applied. Regarding the maturity group, highest effects were registered in the FAO groups 500 and 600, 20%, and lowest effects were seen in the groups 300 and 400, 16 and 13%, respectively. Early corn hybrids mature in late August or early September and they avoid effects of drought that almost regularly occurs in August. With the later-maturing hybrids, the irrigation practice increased the yield by about 1 t/ha on average.